1993
DOI: 10.1111/j.2042-7158.1993.tb05685.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Wound Healing: Some Biochemical Parameters in Guinea-pig

Abstract: Hairs were removed from the dorsal skin of guinea-pigs and 5-6 wounds (7 x 7 mm) were surgically induced by totally removing the epidermal and part of the dermal surface. They were then allowed to heal. The newly formed wound tissues were dissected at different times during the process and analysed by biochemical and histological methods. Hydroxyproline, proteins, DNA and semicarbazide-sensitive amine oxidase (SSAO) were measured, as were [14C]leucine and [3H]thymidine incorporation in some samples. The peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The precise mechanism of wound healing is not clearly understood. The process of wound repair appears to be very complex involving various parameters such as inflammations, cell proliferations, collagen lattice formation, microbial infections, oxygen free-radicals, epithelization, anti-oxidant defense and biochemical change in hydroxyproline (Bodeker and Hughes, 1998;Martin, 1996;Clark, 1996;Buffoni et al, 1993). Hence, the existing pharmacological validation of plant active compounds should realize several factor(s) or parameter(s) involved in wound repair.…”
Section: Discussionmentioning
confidence: 98%
“…The precise mechanism of wound healing is not clearly understood. The process of wound repair appears to be very complex involving various parameters such as inflammations, cell proliferations, collagen lattice formation, microbial infections, oxygen free-radicals, epithelization, anti-oxidant defense and biochemical change in hydroxyproline (Bodeker and Hughes, 1998;Martin, 1996;Clark, 1996;Buffoni et al, 1993). Hence, the existing pharmacological validation of plant active compounds should realize several factor(s) or parameter(s) involved in wound repair.…”
Section: Discussionmentioning
confidence: 98%
“…It involves platelet aggregation and blood clotting, formation of fibrin, an inflammatory response to injury, alteration in the ground substances, angiogenesis and re-epithelialization. Healing is not complete until the disrupted surfaces are firmly knit by collagen (Buffoni et al, 1993). The basic principle of optimal wound healing is to minimize tissue damage and provide adequate tissue perfusion and oxygenation, proper nutrition and moist wound healing environment to restore the anatomical continuity and function of the affected part (Pierce and Mustoe, 1995).…”
Section: Pathology Of Woundsmentioning
confidence: 99%
“…Non‐irradiated control rats were left to heal naturally. The previous studies have reported that markers related with wound repair process were found to be prominently expressed in the first week of post‐wounding . Hence, in the present study wound tissues were collected for the evaluation of biochemical and molecular markers after 7 days of post‐wounding.…”
Section: Methodsmentioning
confidence: 95%